The Muslim Approach to the Study of Religions - Amjad Mahmud Hussain, Mohd Aderi Che Noh (International Journal of Advanced Science and Technology, 2020)
This article highlights the need for Muslims to study other religions and philosophies for a number of reasons. This article describes the study of religions by Muslims in the past, and it attempts to explain how Muslims in the past were so successful at studying other faiths. The main aim of the article is to provide a methodology for contemporary Muslims to study the ‘other’. With that in mind the article provides an insight into the contemporary approach towards phenomenology of religion and offers an alternative route to approach the study of religions.